Civil Liability of Palm Oil Companies for Environmental Damage - Aurora Mayawa Rissandjani; Ni Made Jaya Senastri; Ni Komang Arini Styawati (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the harmonization of the principle of strict liability and the principle of onrechtmatige daad in civil liability for environmental damage caused by corporate waste, as well as corporate liability for environmentally friendly products that cause environmental damage. This study employs a normative legal research method using legislative, conceptual, and case-based approaches. The results of the study indicate that the harmonization of these two principles can strengthen the enforcement of environmental law through more effective legal protection for victims of pollution. The principle of strict liability provides an easier burden of proof for victims without requiring them to prove an element of fault, while the principle of onrechtmatige daad continues to serve to assess the existence of a legal violation, negligence, and a causal relationship. Furthermore, the application of strict liability to eco-friendly products plays a crucial role in preventing greenwashing practices, enhancing corporate accountability, and promoting the principles of environmental precaution and sustainability. The harmonization of these two principles reflects the values of justice, legal certainty, and the public interest in achieving environmental protection and sustainable development.